Diffusion Weighted Imaging of the Genitourinary System Techniques and Clinical Applications (Springer International Publishing, 2018)
This book discusses diffusion weighted imaging (DWI) and its evolving clinical role. DWI has frequently been used in the abdomen and pelvis but is now increasingly being used in other clinical applications, especially for the diagnostic workup of oncologic patients. Standardization and clinical validation of quantitative DWI related biomarkers is still ongoing, although efforts have been undertaken, especially in the prostate, to provide standardized imaging guidelines for different clinical indications. The technical aspects and clinical applications of DWI presented focus on the respective anatomical region and its pathologies. The book is unique in providing tables of technical details (imaging protocols, artifacts, optimization techniques) for each chapter, making this complex area as simple and practical as possible. The book is intended for radiologists interested in urogenital radiology and also for radiology residents. .